2016
DOI: 10.1080/15384101.2016.1261767
|View full text |Cite
|
Sign up to set email alerts
|

LZAP is a novel Wip1 binding partner and positive regulator of its phosphatase activity in vitro

Abstract: The phosphatase Wip1 attenuates the DNA damage response (DDR) by removing phosphorylation marks from a number of DDR proteins (p53, MDM2, Chk1/2, p38). Wip1 also dephosphorylates and inactivates RelA. Notably, LZAP, a putative tumor suppressor, has been linked to dephosphorylation of several of these substrates, including RelA, p38, Chk1, and Chk2. LZAP has no known catalytic activity or functional motifs, suggesting that it exerts its effects through interaction with other proteins. Here we show that LZAP bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…GST was from Abcam (Cambridge, MA, USA). Recombinant LZAP was purified from Escherichia coli BL21(DE3) as described in Wamsley et al 35 …”
Section: Methodsmentioning
confidence: 99%
“…GST was from Abcam (Cambridge, MA, USA). Recombinant LZAP was purified from Escherichia coli BL21(DE3) as described in Wamsley et al 35 …”
Section: Methodsmentioning
confidence: 99%
“…CDK5RAP3, also known as LZAP and C53, was first identified as a binding protein of cyclindependent kinase 5 (CDK5) activator (Ching et al, 2000). Subsequent research showed that CDK5RAP3 interacts with a range of proteins, including RelA (Wang et al, 2007), ARF (Wang et al, 2006), Chk1 (Jiang et al, 2005), Chk2 (Jiang et al, 2005), PAK4 (Mak et al, 2011), Wip1 (Wamsley et al, 2017), γ-tubulin (Horější et al, 2012) and p38 MAPK (An et al, 2011). By interacting with these proteins, CDK5RAP3 exerts the role in regulating the cell cycle, cell survival, cell adherence/invasion, tumorigenesis and metastasis (Jiang et al, 2005;Jiang et al, 2009;Liu et al, 2011;Wang et al, 2007Wang et al, , 2006Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, plant PP2Cs are not known to be restricted to specific dephosphorylation motifs and thus are not likely to have the same level of inherent substrate specificity as kinases. However, we are not aware of any systematic analysis to investigate the dephosphorylation specificity of plant PP2Cs, and some mammalian PP2Cs, such as wild type p53‐induced protein 1 (WIP1), are thought to prefer certain types of dephosphorylation sites (see, e.g., Wamsley et al, ).…”
Section: Introductionmentioning
confidence: 99%